Computational Insight to Improve the Thermal Isomerisation Performance of Overcrowded Alkene‐Based Molecular Motors through Structural Redesign. Issue 21 (31st August 2016) - Oruganti, Baswanth; Wang, Jun; Durbeej, Bo
Abstract: Synthetic overcrowded alkene‐based molecular motors achieve 360° unidirectional rotary motion of one motor half (rotator) relative to the other (stator) through sequential photochemical and thermal isomerisation steps. In order to facilitate and expand the use of these motors for various applications, it is important to investigate ways to increase the rates and efficiencies of the reactions governing the rotary motion. Here, we use computational methods to explore whether the thermal isomerisation performance of some of the fastest available motors of this type can be further improved by reducing the sizes of the motor halves. Presenting three new redesigned motors that combine an indanylidene rotator with a cyclohexadiene, pyran or thiopyran stator, we first use multiconfigurational quantum chemical methods to verify that the photoisomerisations of these motors sustain unidirectional rotary motion. Then, by performing density functional calculations, we identify both stepwise and concerted mechanisms for the thermal isomerisations of the motors and show that the rate‐determining free‐energy barriers of these processes are up to 25 kJ mol −1 smaller than those of the original motors. Furthermore, the thermal isomerisations of the redesigned motors proceed in fewer steps. Altogether, the results suggest that the redesigned motors are useful templates for improving the thermal isomerisation performance of existing overcrowded alkene‐based motors. Abstract : Smaller but faster : Reducing the sizes of the rotator and stator halves (see picture) of some of the fastest available overcrowded alkene‐based molecular motors is found to lower the thermal isomerisation barriers by up to 25 kJ mol −1 and facilitate the isomerisation process by reducing the number of steps involved.